Carbonaceous Impurities Contained in Graphene Oxide/Reduced Graphene Oxide Dominate Their Electrochemical Capacitances. Issue 1 (14th June 2013) - Yang, Xiaoyang; Li, Xiaomeng; Ma, Xiao; Jia, Li; Zhu, Liande
Abstract In this article, we report on carbonaceous impurities that residing in graphene oxide prepared from the chemical exfoliation of graphite significantly impact on the electrochemical capacitive qualities of graphene oxide and in situ electrochemically reduced graphene oxide as well. The results demonstrate that the carbonaceous impurities cause totally opposite effects on the electrochemical capacitive properties of graphene oxide and electrochemically reduced graphene oxide. After removal of the impurities, the specific capacitance of graphene oxide is greatly improved while the value for electrochemically reduced graphene is diminished. This finding is particularly favorable to reveal the inherent electrochemical capacitive qualities of graphene and contributes to further exploration of graphene as an electrode material in supercapacitiors.